2015
DOI: 10.1159/000441999
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumoperitoneum due to Constipation

Abstract: We report a rare case of spontaneous pneumoperitoneum. An 82-year-old Japanese male patient was referred to our hospital because of constipation and abdominal pain. Abdominal computed tomography revealed a large amount of feces in the colon and rectum, and free air in the abdomen. Based on these findings, the patient was diagnosed with gastrointestinal perforation. Emergency exploratory laparotomy was performed. Neither perforation nor ischemic changes were recognized in the digestive tract. The patient's defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…It would only make sense if assumed that pneumoperitoneum did not cause her symptoms and resulted as a benign complication of endoscopy. Another possible explanation is that pneumoperitoneum was secondary to constipation, as in the case reported by Yamana et al (7), in which the tomography showed abundant fecal matter in colon and the exploratory laparotomy had no findings; however, that case showed clear acute course, in contrast to our case.…”
Section: Discussioncontrasting
confidence: 69%
“…It would only make sense if assumed that pneumoperitoneum did not cause her symptoms and resulted as a benign complication of endoscopy. Another possible explanation is that pneumoperitoneum was secondary to constipation, as in the case reported by Yamana et al (7), in which the tomography showed abundant fecal matter in colon and the exploratory laparotomy had no findings; however, that case showed clear acute course, in contrast to our case.…”
Section: Discussioncontrasting
confidence: 69%
“…3,4 The SP may be commonly observed after the post-abdominal surgery, postcolonoscopy, peritoneal dialysis and blunt trauma. [1][2][3]6 The SP may occur when air passes upward through genital tract via the uterus and fallopian tubes. Unlike to adult cases with SP, gynecologic etiologies of SP are rare in pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, one adult case has been reported showing a relationship between SP and PCI induced by constipation. 6 Herein, we report a pediatric case with SP. To the best of our knowledge, this is the first pediatric case presentation showing coexistence of SP and PCI induced by constipation.…”
Section: Introductionmentioning
confidence: 96%
“…The intra-thoracic causes include mechanical ventilation, cardiopulmonary resuscitation, and pneumothorax, thought to be dissection into the abdominal cavity via transdiaphragmatic or transmediastinal routes. Abdominal causes include pneumatosis cystoides intestinalis (PCI), jejunal diverticulosis, constipation, and colonic pseudoobstruction [3][4][5][6][7][8][9]. Gynecological causes include sexual activity or spa jet-induced pneumoperitoneum [3,10].…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of these submucosal and subserosal cysts causes pneumoperitoneum. In some pneumoperitoneum cases, diverticular disease and constipation accompany PCI [6,7]. This may be caused by increased intestinal pressure with or without PCI.…”
Section: Discussionmentioning
confidence: 99%